2006
DOI: 10.1042/bj20060137
|View full text |Cite
|
Sign up to set email alerts
|

New ways to print living cells promise breakthroughs for engineering complex tissues in vitro

Abstract: The ability to control the placement of cells and the assembly of networks in vitro has tremendous potential for understanding the regulation of development as well as for generating artificial tissues. To date, most engineering tools that can place materials with precision are not compatible with the requirements of living cells, and so approaches to tissue engineering have focused on patterning substrates as a way of controlling cell growth rather than patterning cells directly. In this issue of Biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Various printing and rapid prototyping technologies have been adapted for use in 3D bioprinting strategy. In situ skin printing of full-thickness wound closure with vascularization [33] Mouse full-thickness wound LIFT Keratinocyte, fibroblasts Collagen 10×10×2 mm 3 Multi-layered epidermis tissue construction [4,32] Mouse full-thickness wound Jetting Keratinocyte, fibroblasts, ECs Collagen 17×17 mm 2 Microvasculature in a bilayer skin graft, resulting in improved wound contraction [68] In vitro skin model Extrusion Keratinocyte, fibroblasts Collagen 10×10 mm 2 Dermal/epidermal-like distinctive layers [19] In vitro skin model Jetting Keratinocytes, fibroblasts Collagen 6×6 mm 2 Dermis and epidermis layers [20] Adipose tissue Mouse subcutaneous implantation Extrusion ADSCs Decellularized adipose tissue matrix, PCL 10 (D)× 5 mm (H) Precisely-defined and flexible dome-shape structure and adipose tissue formation in vivo [34] Skeletal muscle Rat ectopic implantation Extrusion C2C12 myoblasts Fibrin 15×5×1 mm 3 Myotybes formation with high alignment [3] In vitro LIFT+ manual seeding C2C12 myoblasts…”
Section: Bioprinting Methods For Cell Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Various printing and rapid prototyping technologies have been adapted for use in 3D bioprinting strategy. In situ skin printing of full-thickness wound closure with vascularization [33] Mouse full-thickness wound LIFT Keratinocyte, fibroblasts Collagen 10×10×2 mm 3 Multi-layered epidermis tissue construction [4,32] Mouse full-thickness wound Jetting Keratinocyte, fibroblasts, ECs Collagen 17×17 mm 2 Microvasculature in a bilayer skin graft, resulting in improved wound contraction [68] In vitro skin model Extrusion Keratinocyte, fibroblasts Collagen 10×10 mm 2 Dermal/epidermal-like distinctive layers [19] In vitro skin model Jetting Keratinocytes, fibroblasts Collagen 6×6 mm 2 Dermis and epidermis layers [20] Adipose tissue Mouse subcutaneous implantation Extrusion ADSCs Decellularized adipose tissue matrix, PCL 10 (D)× 5 mm (H) Precisely-defined and flexible dome-shape structure and adipose tissue formation in vivo [34] Skeletal muscle Rat ectopic implantation Extrusion C2C12 myoblasts Fibrin 15×5×1 mm 3 Myotybes formation with high alignment [3] In vitro LIFT+ manual seeding C2C12 myoblasts…”
Section: Bioprinting Methods For Cell Printingmentioning
confidence: 99%
“…Tissue engineering and regenerative medicine aim to meet the demand for replacement of tissues or organs. In the last decade, there are various advanced technologies which are producing remarkable success outcomes in the field [1,2]. Among these, three-dimensional (3D) bioprinting technologies for fabricating tissue constructs are a most advanced technique that has potential to accelerate the clinical translation, because these technologies are continually demonstrating the feasibility of building complex tissue constructs at sizes and shapes, which can be anatomically and clinically applicable [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering and tissue models are two obvious and potentially useful applications for organoids. Tissue engineering seeks to recapitulate tissues and organs in functional ways for the purpose of replacing or repairing injured tissues and organs [3,4]. Tissue models have various uses in toxicology and pharmacokinetic studies for the purpose of representing native tissues and organs while not involving human subjects and minimizing reliance on nonhuman mammals [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In addition, the ability of inkjet printing to maintain control over spatial parameters while printing 2- and 3D structures indicates that it has great potential toward advanced tissue engineering applications such as organ printing. 6 Even greater opportunities exist for inkjet printing of controlled drug delivery systems and precision dosing. 7 Research has shown that inkjet printing has the potential to increase efficiency and bioavailability, as well as decrease overall waste 8,9 of pharmaceutical compounds.…”
Section: Introductionmentioning
confidence: 99%